Meningkatkan Kreatifitas Peserta Didik Pada Pembelajaran Pak Dan Bp Dengan Metode Pbl Kelas VIII SMP Negeri 1 Siempatnempu - Pasti Melina Nainggolan; Timotes Tote Jelahu; Modestus Haryono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Education is one of the basic needs required by every human being and an obligation that must be obtained by every citizen. The development of human life from time to time is certain to be more complex, especially in the development of science and technology. This requires humans to always be able to compete in keeping up with developments and be able to survive by being able to solve all the problems they face. Therefore, a student's ability to think critically is an important and primary thing. Critical thinking skills will be very beneficial for students because they will understand a problem in detail, so it is expected that students will find it easier to solve the problem. For this reason, learning that emphasizes critical thinking skills must be implemented in schools, especially at the junior high school level, which is the middle level of education and is a stepping stone to a wider social interaction. The purpose of this study was to determine the effect of applying the Problem-Based Learning model in improving critical thinking attitudes in Catholic Religious Education and Ethics learning for seventh-grade students with the theme